Towards Safer Gene Therapies: Investigating Human Cell Type Effects on CRISPR-Cas9 Off-Target Editing - Stevrell, Julia (My University, 2023)
The CRISPR-Cas9 technology for precise and efficient genome editing holds immense potential in a vast range of bioscience applications, including the therapeutic treatment of somatic genetic disorders by directly correcting disease-causing mutations. However, the potential for CRISPR-Cas9-based gene therapies is largely limited by the risk of introducing unintended mutations at off-target genomic sites. These so called off-target effects (OTE), and their downstream phenotypic implications are key safety concerns for prospective therapeutic applications. Despite extensive research efforts, many potential underlying factors behind CRISPR-Cas9-mediated off-target activity in humans remain unexplored. To the best of our knowledge, cellular heterogeneity is one such incompletely evaluated factor. As such, this thesis project aimed to investigate the potential influence of different cell types on the off-target activity of both target-specific and unspecific (’promiscuous’) CRISPR-SpCas9 genome editors. To this end, three different human cell lineages; ventricular cardiomyocytes, hepatocytes, and midbrain dopaminergic neurons, were generated from previously established engineered human induced pluripotent stem cell (hiPSC) lines through directed differentiation. hiPSC line generation followed a dual approach with TETON controlled expression of SpCas9 and U6-controlled expression of cell line-specific sgRNAs (PCSK9, VEGFA2, or HEK4) for transient, doxycycline-inducible genome editing in mature cell types. Differentiated cell types were partly validated with comparative gene expression and protein expression assays and subsequently assessed for on- and off-target editing with short-read, targeted Next-Generation Sequencing methods. On-target editing was validated with Amplicon-seq and showed significant cell type- and batch-dependent induction efficiencies as well as considerable leakage-mediated editing across cell types. Guide-specific off-target cleavage sites were identified with CHANGE-seq and cross-validated with independent methods. Small indel and SNP mutations at on- and off-target loci were verified with the rhAmpSeq assay and resulting OTE profiles were compared between cell types. Several significant cell type-specific off-target edits were detected for both target specific and unspecific CRISPR-SpCas9. Although further validation is needed,the identified cell type-specific edits suggest that the cell type has an influence on CRISPR-Cas9 off-target nucleolytic activity. These findings could have considerable implications for continued research into the safety of CRISPR-Cas9 genome editors, and nevertheless their clinical use for combating genetic diseases.
Keywords: CRISPR-Cas9; differentiation; doxycycline; off-target editing; CHANGE-seq; rhAmpSeq; next-generation sequencing; hiPSC